Effect of different pre-treatment methods on gasification properties of grass biomass. (June 2021) - Sibiya, N.T.; Oboirien, B.; Lanzini, A.; Gandiglio, M.; Ferrero, D.; Papurello, D.; Bada, S.O.
Abstract: The effect of different pre-treatments method on the gasification efficiency of grass biomass have not previously been evaluated. In this study, the effect of three different pre-treatment methods on gasification properties of grass biomass was investigated under CO2 conditions. The pre-treatment methods were dry torrefaction, wet torrefaction, and leaching (chemical). The results obtained showed that the heating values increased by 2, 77% in the leached grass, 8, 3% in the dry torrefied grass and 13, 5% in the wet torrefied grass. However, the wet torrefaction had the highest reactivity index of 0, 25 followed by dry torrefaction 0, 182, then leaching 0, 156. The effect of the different pre-treatment on activation energy showed that the activation energy of raw grass biomass was reduced from 161, 7 kJ/mol to 141.5 kJ/mol for leached grass, 124.3 kJ/mol for dry torrefied and 86.97 kJ/mol for wet torrefied grass. These results show that wet torrefaction can improve gasification properties significantly when compared to dry torrefaction and leaching. The pore structure and pore volume effect of treated biomass was likely the predominant reason for the better char reactivity and conversion during gasification of wet torrefied sample. The research supplied an insight into the effect of different pre-treatment methods on grass biomass gasification. Highlights: Effects of different pretreatment methods on gasification properties of grass were evaluated. The three pretreatment methods are dry torrefaction, wet torrefaction, and chemical leaching. Wet torrefaction improved gasification properties more than dry torrefaction and leaching. Wet torrefaction had the highest reactivity index of 0.25; dry torrefaction 0.18; leaching 0.16